ANALISIS PENGARUH LAYANAN I-BANKING, M-BANKING, DAN FASILITAS ATM TERHADAP KEPUASAN NASABAH (STUDI KASUS NASABAH BANK BTN KCP TULUNGAGUNG) - Eryaningtyas, Nadia Salsabela; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2023)
The pattern of human’s behavior in using electronic services to acquire various kinds of information is affected by the rapid technological advancement. This is beneficial for, particularly banking, industries, as evidenced by the fact that banks nowadays come up with cutting-edge services such as internet banking and mobile banking. The sample of this quantitative descriptive research was selected using non-probability sampling, while the data was examined using factor analysis in SPSS version 15.0 of 2023. The result of the F test (simultaneous) is 56.554, which is greater than the F table of 2.699, and therefore H0 is rejected, and H1 is accepted. As the significance value of 0.000 is smaller than 0.05, internet banking, mobile banking, and ATM facilities simultaneously have a significant effect on the satisfaction of customers at the sub-branch office of Bank BTN in Tulungagung. Despite the positive and significant effect of the three variables, mobile banking is more preferable for some customer groups. In addition to its practicality, the service is helpful when they are in a difficult condition. In the future, the bank will develop a service where facilities in the internet banking will be integrated into its mobile banking application for greater customer benefit and ease